Effect of fertilizatin and Rhizobium inoculation on the growth of Leucaena and Gliricidia on an Alfisol in southwestern Nigeria - Cobbina, J.; Mulongoy, K.; Atta-Krah, A.N. (1992)
The aim of the research reported here was to compare the early growth and nodulation of Leucaena leucocephala and Gliricidia sepium, grown in pots containing soils of differing fertility obtained from alley farms. The plants' response to nitrogen and phosphorus fertilizers and to inoculation with rhizobia was also assessed. The application of the fertilizers, separately or combined, in the low-fertility soil increased plant height and shoot dry-matter and nitrogen yield at 84 days after planting. Inoculation with the Rhizobium strains IRc 1045 (local) and Lx 382 (Nitragin, USA) improved shoot dry-matter and nitrogen yield in some cases but was not as effective as the use of nitrogen fertilizer. There is thus a need to identify more effective strains of Rhizobium for these environments. The application of nitrogen fertilizer decreased nodule numbers on L. leucocephala in the relatively poor soil with or without the phosphorus treatment, but had no effect on the plant's nodule numbers in the relatively fertile soil with the phosphorus treatment. In this zone, phosphorus fertilizer may be necessary to ensure adequate nodulation, nitrogen fixation and plant growth.